Myeloid-derived suppressor cells in ovarian cancer: friend or foe? - Walankiewicz, Monika (Cent Eur J Immunol, 2017)
Although previous decades contributed to major progress in targeted therapy of many malignancies, the treatment of gynaecological cancers remains a challenging task. In the evidence of rising cancer mortality, the search for new methods of treatment is a dire need. Exploring the mechanisms of interaction between tumour cells and host immune response may allow the introduction of new, effective therapies – not as toxic and far more efficient than conventional methods of cancer treatment. Epithelial ovarian cancer (EOC) is typically diagnosed at advanced stages. Its incidence and mortality rate is high. Powerful diagnostic tools for this kind of cancer are still under investigation. Multiple mechanisms existing in the ovarian tumour network create a specific immunosuppressive microenvironment, in which accumulation of myeloid-derived suppressor cells (MDSCs) may be a critical component for diagnosis and treatment. This review attempts to verify current knowledge on the role of MDSCs in EOC.